An investigation of the surface and groundwater leachate from an old waste disposal site at Mamak, Ankara, Turkey. (13th August 2007) - Celik, Mehmet; Tastekin, Metin; Kayabali, Kamil
Mamak solid waste disposal site covers an area of approximately 0.5 square kilometre and the amount of waste it holds is around 13 × 106 m?. The amount of leachate measured through a weir at the toe of the body of waste is 164, 000 m3? per annum. It is calculated that approximately 130, 000 m? of this amount directly comes from the waste. Owing to the retention of precipitation by wastes, it takes about a week for the outflow of the recharge to reach the weir. Analyses of water samples collected through the wet and dry periods during a one-year monitoring period revealed that the hydrochemical facies of leachate is Na+-Cl--HCO3- and Na+-HCO3--Cl- whereas the facies of a nearby creek is Na+-Cl-, Na+-HCO3- and Ca2+-HCO3-; the facies of groundwater is Ca2+-HCO3-. It was determined that as the heavily contaminated leachate is diluted by unpolluted surface and subsurface waters, its hydrochemical facies shifts from Na+-Cl- to Ca2+-HCO3-. The proposed solutions for controlling or mitigating the environmental threat imposed by leachates emanating from Mamak waste disposal site would be either diverting it to the city sewage or, to be a better solution, treating it in a processing plant.